How Does Loss Aversion Mediate the Relationship Between Personality Traits and Efficiency of Skills in Investment Decision- Making? - Jayawardena, A.M.A.; Nanayakkara, N.S. (International Review of Management and Marketing, 2024)
This study examines how loss aversion mediates the connection between personality factors and the effectiveness of investment decision-making skills among individual investors at the Colombo Stock Exchange. This research challenges the neoclassical paradigm that presumes investor rationality. Instead, it accords with behavioural finance, which emphasizes deviations from rationality in both beliefs and preferences. Using Prospect Theory as a framework, this study examines how the five major personality traits -conscientiousness, extraversion, agreeableness, neuroticism, and openness to experience influence investment decision-making. Analyzing data from 351 investors, a structured questionnaire and purposive sampling were used. The analysis was conducted using Structural Equation Modelling with SmartPLS4. The results demonstrate notable correlations: individuals with a higher level of openness to experience and agreeableness tend to have a positive impact on their investment decision-making, whereas extraversion, openness to experience, and conscientiousness are highly associated with loss aversion. Loss aversion plays a crucial role in connecting extraversion, conscientiousness, and openness to experience with investment decision-making. This study enhances the field of behavioural finance by providing a detailed understanding of how personality traits and loss aversion influence investing choices.